The Ideopolitical Differentiation and Violence of The Serbian Rule Against Albanian Lecturers and Students at the University of Prishtina (1981-1990) - Avni REXHA (Celal Öney, 2021)
The years 1966-1974 marked a turning point in the modern history of Kosovo. The political changes in Yugoslavia, which followed the fall of the Serbian hegemonic block, facilitated the efforts of the Albanian population to achieve national and political rights. The opportunity to continue education in the Albanian language was accompanied by the advancement of the constitutional position of the Socialist Autonomous Province of Kosovo within the Yugoslav federation. The opening of the University of Prishtina, the Academy of Sciences, scientific research institutes, cultural institutions, etc., resulted in the raising of the Albanian national consciousness not only in Kosovo but also in other areas inhabited by Albanians in the former Yugoslavia. In 1981, Albanian student demonstrations broke out in Kosovo, the main demand of which was to equalize Kosovo's legal status with other Yugoslav republics. But Yugoslav political circles viewed the demonstrations as an attempt to overthrow Yugoslavia's constitutional order. They were forcibly suppressed. At the same time, Serbian political circles, which had always tried to obstruct Albanian national achievements, took the opportunity to politically attack the University of Prishtina, which they considered a source of Albanian nationalism, and possibly to close it. Many lecturers and students were convicted, imprisoned, and expulsed from the University. Therefore, the paper "The ideopolitical differentiation and violence of the Serbian rule against Albanian lecturers and students at the University of Prishtina 1981-1990" aims to elaborate the approach of Yugoslav communist policy to the 1981 student demonstrations in Kosovo, the Yugoslav state violence against lecturers and students, and the measures that were taken to collapse the University of Prishtina, respectively ideological and political differentiation.